Antihyperglycaemic and tissue-repair effects of Myrmeleon formicarius extract in streptozotocin-induced diabetic mice. Issue 2 (April 2019) - Prihatin, Jekti; Narulita, Erlia; Mufidah, Lailatul; Kurniawan, Alief; Wulandari, Dwi; Hariyadi, Slamet
الملخص: أهداف البحث: تهدف هذه الدراسة إلى دراسة تأثير أخذ المستخلص مايرميليون فورميكاريوس (ليث عفرين) عن طريق الفم على أنسجة الكبد والكلى في الفئران المصابة بالسكري الناجم عن الستربتوزوتوزين. طرق البحث: تم تحضير ٢٤ فأرا عن طريق حقنهم بجرعة واحدة من الستربتوزوتوزين داخل الصفاق وتم تقسيمهم إلى ست مجموعات. مجموعة المراقبة السلبية، ومجموعة المراقبة الإيجابية التي عولجت بغليبينكلاميد. تلقت أربع مجموعات علاجية مستخلص مايرميليون فورميكاريوس (ليث عفرين) بجرعة ٢.٥، و٥، و٧.٥، و١٠ مجم/كجم من وزن الجسم، على التوالي. ثم استخدمت مقاطع رقيقة دائمة لدراسة أنسجة الكبد والكلى للفئران. النتائج: أظهرت النتائج أن الجرعة الأنسب لخفض مستويات الجلوكوز في الدم بعد يومين من العلاج كانت ١٠ مجم/ كجم من وزن الجسم لمستخلص مايرميليون فورميكاريوس (ليث عفرين). أظهر الفحص النسيجي للكبد والكلى أن مستخلص ليث عفرين ١٠ مجم/كجم من وزن الجسم و٥ مجم/كجم من وزن الجسم ينتج تأثيرات إصلاحية أكثر على الأنسجة التالفة. الاستنتاجات: مستخلص مايرميليون فورميكاريوس (ليث عفرين) كانت له القدرة على خفض مستوى السكر في الدم كما كانت له أيضا القدرة على إصلاح تلف الأعضاء الناجم عن ارتفاع السكر في الدم. Abstract: Objectives: In this study, we aimed to investigate the effects of oral administration of Myrmeleon formicarius (antlion) extract on liver and kidney histology in streptozotocin-induced diabetic mice. Methods: Twenty-four mice received a single intraperitoneal injection of streptozotocin and were then divided into six groups. Untreated diabetic mice served as the negative control group, and glibenclamide-treated mice served as the positive control group. Mice in the other four groups, namely T1, T2, T3, and T4 groups, received M. formicarius (antlion) extract at 2.5, 5, 7.5, and 10 mg/kg, respectively. Permanent thin sections were used to examine liver and kidney histology. Results: The most appropriate antihyperglycaemic dosage of the M. formicarius extract was 10 mg/kg for 2 days. Histological examination of the liver and kidneys showed that the antlion extract at 10 and 5 mg/kg exhibited significant tissue-repair effects. Conclusion: M. formicarius (antlion) extract can not only reduce blood glucose levels but also repair hyperglycaemia-induced tissue damage.